2016
DOI: 10.1080/14756366.2016.1238366
|View full text |Cite
|
Sign up to set email alerts
|

Isatin thiazoline hybrids as dual inhibitors of HIV-1 reverse transcriptase

Abstract: A series of 3-3-{2-[2-3-methyl-4-phenyl-2,3-dihydro-1,3-thiazol-2-ylidene]hydrazin-1-ylidene-2,3-dihydro-1H-indol-2-one derivatives has been designed and synthesized to study their activity on both HIV-1 (Human Immunodeficiency Virus type 1) RT (Reverse Transcriptase) associated functions. These derivatives are analogs of previously reported series whose biological activity and mode of action have been investigated. In this work we investigated the influence of the introduction of a methyl group in the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Compounds containing these rings have widespread biological applications as anticancer [5153], anti-HIV [5455], anti-inflammatory [56], antimicrobial [5759], and specially antibiotic [6064] agents. Despite their great relevance in drug design, only very few synthetic methods towards these compounds have been reported to date [44].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing these rings have widespread biological applications as anticancer [5153], anti-HIV [5455], anti-inflammatory [56], antimicrobial [5759], and specially antibiotic [6064] agents. Despite their great relevance in drug design, only very few synthetic methods towards these compounds have been reported to date [44].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 1-[(2-methylbenzimidazol-1-yl) methyl]-2-oxo-indolin-3-ylidene]amino]thiourea is an in vitro and in silico ISSN 2056-9890 Chikungunya virus inhibitor (Mishra et al, 2016). The title compound (I), 5-chloroisatin-4-methylthiosemicarbazone, is an intermediate in the synthetic pathway of HIV-1 (human immunodeficiency virus type 1) RT (reverse transcriptase) inhibitor synthesis (Meleddu et al, 2017); a new crystal structure determination is reported here, the original work having been published by Qasem Ali et al (2012). Thus, the crystal structure determination of isatin-thiosemicarbazonebased molecules is an intensive research area in medicinal chemistry and the main focus of our work.…”
Section: Chemical Contextmentioning
confidence: 92%
“…From the early years, the chemistry of isatin-based molecules emerged from the synthetic approach to a large class of organic compounds with applications in biochemistry and pharmacology. For two recent examples, see: 1-[(2-methylbenzimidazol-1-yl) methyl]-2-oxo-indolin-3-ylidene]amino]thiourea, a derivative with in silico and in vitro inhibition of Chikungunya virus replication (Mishra et al, 2016) and 5-chloroisatin-4-methylthiosemicarbazone, another derivative which appears as an intermediate in the synthesis of an HIV-1 RT inhibitor (Meleddu et al, 2017). The abbreviation HIV-1 RT stands for human immunodeficiency virus type 1 reverse transcriptase.…”
Section: Chemical Contextmentioning
confidence: 99%